The effects of hog manure ammonium sulfate and complete fertilizer on the growth and yield of IR66 - Rola, Salve M. (Animo Repository, 1989)
An area of 100 sq.m. is utilized for the study to compare the effects of hog manure, ammonium sulfate and complete fertilizer on the growth and yield of IR66.The Randomized Complete Block Design was employed in the study. The treatments used were as follows : treatment A (Control), treatment B (Hog Manure), treatment C (Ammonium sulfate) and treatment D (Complete Fertilizer). The ANOVA showed that plants treated with complete fertilizer had the highest average plant height, average leaf area and average grain yield. Plants treated with hog manure had the highest average number of leaves and average number of productive tillers. Plants treated with ammonium sulfate had the highest average number of tillers. Fertilizers, either inorganic or organic had an effect on vegetative growth of IR66 grown in a 100 sq. m. area (0.01 ha) in an irrigated ricefield in Bicol.